Monitoring the beautiful adapted game: a 3-year prospective surveillance study of injuries in elite English Para football - Weiler, R.; Verhagen, E.; Taylor, A.; Ahmed, O.-H. (Science and Medicine in Football, 2022)
Para football is currently played in impairment-specific formats by thousands of people worldwide. To date, there have been no prospective longitudinal injury surveillance studies. This study aimed to implement a prospective injury surveillance study within elite English Para football and analyse the injury risk within the England Blind and Cerebral Palsy (CP) squads. Match and training injury data based on a `time loss` definition were collected and analysed for each squad including incidence per 1,000 player hours, severity, injury location and associated event of injury. Injury incidence were lower in training than matches (CP 67.6/1000 player match hours (CI 33.8-135.2) and 5.7/1000 training hours (CI 3.8-8.7) and Blind 44.0/1000 player match hours (CI 26.1-74.3) and 5.5/1000 training hours (CI 3.5-8.6). Training injuries were more severe than match injuries across both squads (CP median 12days lost in matches and 16 training and Blind median days 5 matches and 12 training). 73% Blind and 74% CP footballer injuries were to the lower limb and 17% head and neck equally across both Para football squads. `Muscle and tendon injuries` (51%) represented the greatest proportion of injuries for CP footballers, and `joint (non-bone)/ligament injuries` (43%) for Blind footballers. Collaboration and implementation of higher quality surveillance methodology and data collection in Para sport with greater athlete numbers are needed to inform injury prevention strategies.